Novel Insights on Chronic Kidney Disease, Acute Kidney Injury and Polycystic Kidney Disease - Vijayakumar, Soundarapandian (IntechOpen, 2012)
This book offers novel insights on topics such as congenital obstructive nephropathy, cerebral-renal salt wasting, and the role of hemoglobin variability in clinical outcomes of CKD which are not very often discussed in the literature. With comprehensive and insightful reviews by eminent clinicians and scientists in the field, this book is a valuable tool for nephrologists.